The Influence of Motivation, Self-Efficacy, and Social Media Utilization on Business Interest Among Generation Z Students in the Business Administrasion Program at UPN “Veteran” Jawa Timur - Andri Rizal Setiawan; Acep Samsudin (Lavish Opulent Education, 2025)
This study aims to identify and analyze the influence of Motivation, Self-Efficacy, and the Social Media Utilization on the Entrepreneurial Interest of Generation Z among Business Administration students at UPN